PENENTUAN PREMI TUNGGAL BERSIH UNTUK KONTRAK ASURANSI JIWA SEUMUR HIDUP UNIT LINK DENGAN BENEFIT DIAKHIR 1/M TAHUN KEMATIAN - , YAYUK ROSANAWATI; , Dr.Gunardi, M.Si, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Unit-linked life insurance is an insurance product that combines life insurance with an investment element. This thesis concentrates on unit-linked insurance, starting with the model construct and prove the value of the net single premium unit-linked life insurance and the value of benefit. Where the age of a person linked on the call option, and then by using a simulation of the stock price, we'll get of net single premium and benefits. Customers can consider when it is appropriate to follow the program, determines the selected stock, look at volatility, including considering the exercise price, the risk free interest rate and the time of exercise . This research be concluded that the net single premium prices will be more expensive if the age of the insured is getting older, the volatility of stock returns, warranty desired, and the risk-free interest rate higher but the lower exercise price . The benefit received is a return of premium guarantee appropriate percentage agreed plus the value of call option profit, if the customers want to exercise option.